Correction to: Intrauterine resuscitation during the second stage of term labour by maternal hyperoxygenation versus conventional care: study protocol for a randomised controlled trial (INTEREST O2) - Lauren M. Bullens; Alexandra D. J. Hulsenboom; Suzanne Moors; Rohan Joshi; Pieter J. van Runnard Heimel; M. Beatrijs van der Hout-van der Jagt; Edwin R. van den Heuvel; S. Guid Oei (Trials, 2018)
Following publication of the original article [1], the authors noticed that the sample size for the study group was incorrectly reported in the Methods section.